Mulheres negras e suas práticas de socialização escolar: afirmando direitos, desafiando preconceitos - Luzia Maria Alves da Silva (2016)
The general aim of this study was to implement interdisciplinary intervention actions in a public state school, analyzing and trying to understand how the school socialization practices promote social exclusion/segregation of black female students. Using a research-action meth-odology, we start from Thiollent (1985), with the contribution of the use of techniques such as rounds of conversation and focus groups. As a central issue, we reflect on our educational prac-tices that have made us (re)view theories and practices, which leads us to perceive new charac-terizations of gender and ethnic-racial issues. The benchmark is based on reading discussions of authors like Munanga (2008, 2009), Blonde (2003), Beauvoir (1970), Lacan (1964.1972), Thin (2006), Viana (2002) and Setton (2009, 2010), especially when these authors trace their considerations on educational (under)achievement in well-populated areas and the constitution of the woman as subject, as well as gender constitution and ethnic-racial issues. As a result, we realized that the intervention worked and provided us with moments to reflect on our educa-tional practices and, above all, behaviors in the social environments we live in, showing that the school has offered a guarantee of inclusion and a measure of permanence. However, social-ization practices that are developed in school have not secured the overcoming of inequalities or favored social inclusion of black women with low income.